2022
DOI: 10.1002/slct.202103963
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Healing Clay/Epoxy Composites Prepared from Clay‐Modified Microcapsules

Abstract: Urea‐formaldehyde microcapsules were made in the presence of montmorillonite (MMT) nanoparticles by in‐situ polymerization and characterized with different methods. To monitor the presence of MMT and Dicyclopentadiene in microcapsules. Fourier‐transform infrared spectroscopy (FTIR) spectra was taken from samples. Distribution of microcapsule‘s diameters was studied by optical microscopy (OM) micrographs. Size distribution analysis showed that the average diameter of the microcapsules decreased from 130 (in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Raj Kumar et al, have reported epoxy-PMMA based microcapsules with healing efficiencies of neat epoxy and CFRP with microcapsules were 72% and 53%, respectively [22]. DCPD-Montmorillonite (MMT) nanoparticle-based microcapsules showed a decrease in diameter and better response to temperature [23,24]. Our previous studies have shown that dual-core microcapsules containing DCPD-CNT and UF resulted in improved thermal and electrical properties with the incorporation of MWCNT [25].…”
Section: Introductionmentioning
confidence: 99%
“…Raj Kumar et al, have reported epoxy-PMMA based microcapsules with healing efficiencies of neat epoxy and CFRP with microcapsules were 72% and 53%, respectively [22]. DCPD-Montmorillonite (MMT) nanoparticle-based microcapsules showed a decrease in diameter and better response to temperature [23,24]. Our previous studies have shown that dual-core microcapsules containing DCPD-CNT and UF resulted in improved thermal and electrical properties with the incorporation of MWCNT [25].…”
Section: Introductionmentioning
confidence: 99%
“…Organic polymers such as urea-formaldehyde (UF), polyurethane, polyurea and melamine-formaldehyde are used to form the shell of MCs (Zhang et al, 2022;Lee, 2001). UF resins in this shell material are preferred because of their fast curing, high reactivity, nonflammability and low cost (Khostavan et al, 2022). Emulsion polymerization is utilized to generate a UF shell by aggregation and condensation processes.…”
Section: Introductionmentioning
confidence: 99%
“…, 2022; Lee, 2001). UF resins in this shell material are preferred because of their fast curing, high reactivity, nonflammability and low cost (Khostavan et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%